2013
DOI: 10.1007/s00705-013-1786-4
|View full text |Cite
|
Sign up to set email alerts
|

Telbivudine and adefovir combination therapy for patients with chronic lamivudine-resistant hepatitis B virus infections

Abstract: We evaluated second-line salvage therapy with adefovir + telbivudine (group 1), adefovir followed by adefovir + telbivudine (group 2), or lamivudine + adefovir followed by adefovir + telbivudine (group 3) in hepatitis B patients with an inadequate virologic response to lamivudine treatment. Simple linear regression analysis showed that for each additional month of treatment, the most significant reduction in viral load occurred in group 1 (HBV DNA [Log10 IU/mL]: group 1, −0.149; group 2, -0.081; group 3, −0.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Chen et al [44] had the similar conclusion that prolonged combination therapy (LAM+ADV and LdT+ADV) was more effective than monotherapy (ADV), regardless of the ALT normalization rate, sustained viral response, or resistance rate. Our previous study, despite the smaller number of patients, demonstrated that LdT+ADV is a suitable second-line salvage therapy for LAM-resistant patients [45]. In our present study, we found the similar effect in terms of HBeAg seroconversion, HBV DNA undetectable rate, and/or ALT normalization rate in the LdT+ADV and LAM+ADV groups after 48 or 96 weeks of treatment ( P <0.05).…”
Section: Discussionsupporting
confidence: 77%
“…Chen et al [44] had the similar conclusion that prolonged combination therapy (LAM+ADV and LdT+ADV) was more effective than monotherapy (ADV), regardless of the ALT normalization rate, sustained viral response, or resistance rate. Our previous study, despite the smaller number of patients, demonstrated that LdT+ADV is a suitable second-line salvage therapy for LAM-resistant patients [45]. In our present study, we found the similar effect in terms of HBeAg seroconversion, HBV DNA undetectable rate, and/or ALT normalization rate in the LdT+ADV and LAM+ADV groups after 48 or 96 weeks of treatment ( P <0.05).…”
Section: Discussionsupporting
confidence: 77%
“…In a small prospective study that compared an adefovir-plus-telbivudine combination-therapy group (n=21) with an adefovir-monotherapy group (n=21), the HBV undetectable rate (<300 copies/mL) was 38.5% and 0%, respectively, and adefovir resistant virus was detected in 9.6% of patients in the adefovir-monotherapy group after 96 weeks [ 294 ]. Two small prospective studies revealed that the reduction in HBV load was greater in the adefovir-plustelbivudine combination-therapy group than the adefovir-plus-lamivudine combination-therapy group [ 295 , 296 ].…”
Section: Management Of Antiviral-resistant Chbmentioning
confidence: 99%
“…The selection of an appropriate treatment strategy is critical for patients with chronic hepatitis B. The management of patients with HBV infection should involve a treatment that consistently reduces the viral load and prevents the development of mutations, which may result in drug resistance [26]. A number of studies have demonstrated that ADV+ETV rescue therapy is efficient for HBV patients resistant to ETV [27−30].…”
Section: Discussionmentioning
confidence: 99%